TELPA: da central passo a passo a central digital. Efeitos da inovação tecnológica sobre o processo de trabalho - Dowling, Juan Alfonso (1989)
This thesis analises the problems related to work organization after the introduction of new tecnologies, with empirical study towards telecommunication companies. The subject of analysis vas Telecomunicações da Paraiba S/A TELPA, wich after 1986 engaged in an informatization process, modernising its operacional structure, incorporating advanced technology - digital main board control, optic fiber, as well as using automated procedures in office work. In our theoretical reflections, essentialy two main subjets were considered: a) the analysis of work on telecommunication, as being part of services, in the optics of productive work versus improductive work, showing that, under certain conditions, the telecommunication work becomes part of society's world of material production and reproduction; being therefore productive work; b) the increasing of problems due to the usage of technology as a way to better control the work force, diverting from de deterministic interpretation which conditions the work organization to the technological matrix. It is pointed out, also, the idea that to a same technology can correspond several alternative forms work organization. On the concrete analysis of Telpa's case, it was concluded that the modernization process being carried out implies into changes such as: new features in the qualification of some workers, increase in the intensity of work and relatie unemployemenet.